Problematika Implementasi Kurikulum Merdeka Belajar di Perguruan Tinggi - Sabriadi HR HR; Nurul Wakia (Adaara: Jurnal Manajemen Pendidikan Islam, 2021)
The discussion in this article is motivated by the existence of an Independent Learning Curriculum (Kurikulum Merdeka Belajar) policy, one of which will be implemented in universities. Specifically, it will reveal various problems in the implementation of the Independent Learning Curriculum in universities.The method used in this study is a literature review or library in which data collection is obtained from various appropriate literature, both in the form of written text and soft copy. Through a literature study that has been carried out by the author, it can be seen that the Independent Learning Curriculum policy includes the provision of autonomy for State University (PTN) or Private University (PTS) to open new study programs provided that the university is accredited A or B and has collaborated with organizations or universities that are included in the QS top 100 world Universities;higher education re-accreditation system is automatic for all ranks except for PT and study programs that will be promoted; freedom to become a State University with Legal Entity(PTN-BH); and the right to study three semesters outside the study program. The problems of implementing the Independent Learning Curriculum in Higher Education are a) the mechanism of collaboration between universities and study programs with parties outside the campus; b) paradigm shift in PTN with legal entities to compete on an international scale; c) internship mechanism outside the study program.